Improved MAUT Framework for Quality Evaluation of University Party Building Work in the New Era Based on the Interval Neutrosophic Multi-Attribute Group Decision-Making - Yao Mo (Neutrosophic Sets and Systems)
In the new era, the evaluation of the quality of party-building work in universities focuses on trengthening political, ideological, and organizational construction. By using a scientific evaluation system, it ensures the implementation of Party theories and policies. It emphasizes innovative methods to enhance Party members' ideological awareness and organizational skills, promoting the integration of Party building with education. This ensures the Party's leadership plays a central role in all university activities, driving comprehensive development. The quality evaluation of university party building work in the new era is a multi-attribute group decision-making (MAGDM) problem. Recently, both the MAUT method and the average approach have been applied to solve MAGDM challenges. Interval Neutrosophic Sets (INSs) are utilized to represent uncertain data during the quality evaluation of university party-building work in the new era. In this study, the MAUT method is adapted for MAGDM with INSs. Furthermore, the Interval Neutrosophic Number MAUT (INN- MAUT) approach is developed for MAGDM. The average approach is used to determine the criteria weights within the INS framework. Finally, a numerical example is provided to demonstrate the application of the INN- MAUT approach in the quality evaluation of university party-building work in the new era. The key contributions of this study include: (1) the development of a MAGDM method using the INN- MAUT approach with INSs, (2) the application of the average method to compute weights under INSs, and (3) the proposal of a novel MAGDM approach for quality evaluation of university party building work in the new era using the INN- MAUT method.